Obtenção Automática da Rede de Drenagem a Partir de Modelos Digitais de Altitude - SKROCH, LUCIENE DELAZARI; DALMOLIN, QUINTINO; VIEIRA, ANTONIO JOSÉ BERUTTI (Pesquisas em Geociências, 1998)
The extraction of drainage network based on manual techniques is a tedious and time consuming task. Some methods are available in the literature to automatically extract drainage networks from Digital Elevation Models (DEM), but the main software developed in Brazil aiming at generation of cartographic data base and Geographical Information Systems (GIS), do not deal with this kind of approach. The SKEL program, a software developed at the Israel University in order to provide drainage network based on DEM, is an alternative option which deserves to be evaluated. Thus, a DEM from an area of about 35km2 was selected for the evaluation. The results of investigation have shown that the approach can be used for the extraction of drainage networks, but some drawbacks were detected, mainly related to the intermediate steps of files conversion and the DEM generation.